Basic Income as a Prologue to Social Policy of the 21st Century - Elena Nazarbaeva (Journal of Economic Sociology, 2018)
The conference “Basic Income as a Prologue to Social Policy of the 21st Century” took place in the Higher School of Economics. It was devoted to both the theoretical and practical aspects of basic income implementation. The conference was organized by the Institute for Social Policy NRU HSE, the European Dialogue Expert Group, and the German Friedrich Ebert Foundation in Russia. According to the opinion of Evgeny S. Gontmakher, professor of NRU HSE, until now, there were no such large-scale discussions on this topic. The conference was attended by a wide range of participants from the academic and political sphere as well as by public representatives. Basic income is treated not only as a new measure of social support but as a part of new social policy emerging in the context of income disparities; job automation that changes the conditions and the structure of employment; and population aging. Interconnections of basic income with inequality and pension-system adaptation were discussed as well attempts and examples of foreign projects in the field in Switzerland and Finland.The presentations provided the ability to dispel the myths about basic income, evaluate the effects of its implementation, look at it as a tool for solving different social problems, and formulate the questions that should be asked while constructing such measures of social support. The potential of basic income as a system for the Russian population was also discussed. Most conference participants agreed that it is not an issue for the near future, and a lot of questions need to be analyzed first.